Insights into Corrosion Inhibition Behavior of a 5-Mercapto-1, 2, 4-triazole Derivative for Mild Steel in Hydrochloric Acid Solution: Experimental and DFT Studies - Israa Abd Alkadir Aziz; Iman Adnan Annon; Makarim H. Abdulkareem; Mahdi M. Hanoon; Mohammed H. Alkaabi; Lina M. Shaker; Ahmed A. Alamiery; Wan Nor Roslam Wan Isahak; Mohd S. Takriff (Lubricants, 2021)
A triazole heterocyclic compound namely 3-(4-ethyl-5-mercapto-1, 2, 4-triazol-3-yl)-1-phenylpropanone (EMTP) was examined for its corrosion protection of mild steel (MS) against 1 M hydrochloric acid medium using gravimetric techniques. EMTP exhibited excellent corrosion protection performance at low and high concentrations towards MS in HCl solution. Comparison of corrosion protection performance of EMTP and its parent triazole and temperature effects of on inhibition efficacy were also studied. EMTP has potential corrosion inhibitor for mild steel in 1.0 M hydrochloric acid solution with the highest protection efficacy of 97% at 303 K. The weight loss findings implied that EMTP protects the metal surface corrosion through the creation of a protective layer at the surface mild steel–corrosive solution interface. The inhibitive efficacy increases with the increase of inhibitor concentration and decreases with increased temperature. The adsorption of EMTP on the surface of MS follows Langmuir’s adsorption isotherm process. DFT method was conducted on EMTP molecule to calculate the quantum chemical parameters and to determine the relationship between the molecular structure of EMTP and protection performance. The molecular parameters, such as energy gap and frontier molecular orbital (highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO)), and the absolute electronegativity (χ) value from inhibitor molecules to unoccupied d-orbital of iron atoms on the mild steel surface were also determined and correlated with protection efficiency. The theoretical findings revealed that the protection performance of EMTP increased with the increase in HOMO energy, and the nitrogen, oxygen and sulfur atoms are most probable positions for bonding through giving electrons to the d-orbital of iron atoms on the mild steel surface.